2013
DOI: 10.1111/jop.12080
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of odontoblastic cells, which indicate odontoblast features both in vivo and in vitro

Abstract: Tooth tissue engineering offers very attractive perspectives for elaboration of regenerative treatments, which enables to cure tooth loss and restore quality of life of the patients. To elaborate such treatment, isolation and culture of dental pulp cell must be achieved as a key element. In this article, we report the establishment of a stable cell line from GFP transgenic rat dental pulp, named TGC (Tooth Matrix-forming, GFP Rat-derived Cell). TGCs have exhibited odontoblastic feature both in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…[27][28][29] Tsujigiwa et al 30 reported that transplanted rat dental pulp cell in SCID mice with b-TCP particles formed dentin-like and pulp-like structure with lining odontoblast. Beta-tricalcium phosphate (b-TCP), produced by Shanghai Bio-lu Biomaterials Co, Ltd., have received great attention as grafts for the reparation and reconstruction of bone, cartilage and other tissues, as well as for filling bone defects due to its excellent biocompatibility and osteoconduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Tsujigiwa et al 30 reported that transplanted rat dental pulp cell in SCID mice with b-TCP particles formed dentin-like and pulp-like structure with lining odontoblast. Beta-tricalcium phosphate (b-TCP), produced by Shanghai Bio-lu Biomaterials Co, Ltd., have received great attention as grafts for the reparation and reconstruction of bone, cartilage and other tissues, as well as for filling bone defects due to its excellent biocompatibility and osteoconduction.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of β‐TCP bioceramics using as bone regeneration scaffolds since fully interoperability globular pore structure allows tissue infiltration and exhibits good osteoconductive capability . Tsujigiwa et al reported that transplanted rat dental pulp cell in SCID mice with β‐TCP particles formed dentin‐like and pulp‐like structure with lining odontoblast. Zheng et al proved that porcine deciduous pulp stem/progenitor cells mixed with β‐TCP significantly regenerated the dentin‐like structures and nearly completely restored the pulp chamber roof defects.…”
Section: Introductionmentioning
confidence: 99%
“…Animal DPSCs have also been tested in several in vivo experiments for regenerative endodontics [ 41 46 ]. DPSCs might have possible application in bone regenerative procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Many bone marrow-derived cells are also present in the dental pulp, and dental pulp stem cells have been confirmed to also differentiate into hard tissue-forming cells. These cells also have the potential for use in bone tissue repair [ 13 ].…”
Section: Introductionmentioning
confidence: 99%